In vitro evaluation of Napier grass-oil palm frond combination as ruminant feed - Wong, Meng Joo; Rajion, Mohamed Ali; Leong, Zi Ping; Ebrahimi, Mahdi; Goh, Yong Meng (2012)
The effects of different combinations of Napier grass (Pennisetum purpureum) and oil palm (Elaeis guineensis Jacq) fronds on ruminal fermentation patterns in vitro in goats were investigated. Rumen liquor from three 2-year-old Kacang-crossbred goats was mixed with buffer and substrates. Four dietary treatments were compared namely 100% concentrates (CON), 50% OPF with 50% concentrates (OPF 50), 50% Napier grass with 50% concentrates (NP 50), and 25% Napier grass, 25% OPF and 50% concentrates (NP-OPF)). Incubation of the mixture was carried out at 39°C for 24 h. Total gas production (GP) was recorded after 2, 4, 6, 8, 10, 12 and 24 h of incubation. Rumen fluid pH, methane gas, total volatile fatty acids and in vitro dry matter digestibility (IVDMD) were determined at the end of incubation. Long chain fatty acid (LCFA) profiles were obtained in separate runs to determine the apparent biohydrogenation (BH) of linoleic (C18:2n-6) and α-linolenic acids (C18:3n-3). Cumulative gas production was significantly higher for the CON group (P<0.05) but not significantly different in the other groups. The NP 50 diet produced significantly higher methane (P<0.05) while other groups did not differ significantly. For IVDMD, the NP-OPF group had a significantly higher digestibility than the NP 50 and OPF 50 groups. Rumen fluid pH, total VFA and apparent BH values for all treatments were not significantly different. In conclusion, the Napier-OPF combination represents a suitable feed for the small ruminant sector in Malaysia but more studies need to be done on effects of OPF on rumen biohydrogenation.